A typology of domestic private land-based investors in Africa: Evidence from Tanzania's timber rush - Justin Edward Lusasi; Esbern Friis-Hansen; Rasmus Hundsbæk Pedersen (Danish Institute for International Studies (DIIS), 2019)
Much attention has been paid to land-based investments - often termed "land grabbing" - in Africa in recent years. However, resent research suggested that the scale of domestic investments may surpass that of foreign investors by far. Our knowledge about these domestic investors - who they are and how they access land - is still limited. In this DIIS Working Paper "A typology of domestic private land-based investors in Africa: Evidence from Tanzania's Timber Rush", PhD student Justin Lusasi, Sokoine University, and DIIS Senior Researchers Esbern Friis-Hansen and Rasmus Hundsted Pedersen review recent literature on land-based investments in Africa and analyze empirical research into land acquired for timber investments in the Southern Highlands of Tanzania. The Working Paper serves the dual purpose of developing a typology of domestic investors involved in tree planting activities in the Southern Highlands that may also help improve our understanding of the diversity of domestic land-based investments in Africa in general. The Working Paper points to significant diversity in regard to how land is acquired among domestic investors and identifies four major types of domestic investors, namely urban-based investors (with no pre-existing ties to the area), urban-based investors originating in the area, resident villagers and religious and government organisations. Each of these four types of domestic investors use different combinations of access mechanisms to acquire land, most importantly capital, social identity and authority. By way of unpacking the diversity of investors the paper suggests that the impact of these investors on local livelihoods differs at the local level. However, more research into the scale and impact of the different types of domestic investors is needed.
Keywords: 330